Abcoronalis protrusus, a new paraboloponine genus and species (Hemiptera: Cicadellidae: Deltocephalinae: Drabescini) from Borneo - Lu, Lin; Zhang, Yalin (Zootaxa, 2018)
The Oriental leafhopper genus Abcoronalis gen. nov. is described and illustrated, and placed in the subtribe Paraboloponina (Cicadellidae: Deltocephalinae: Drabescini). The genus differs from other Paraboloponina in having the coronal suture vestigial and the dorsal margin of the male pygofer with a pair of long, curved processes. The type species, Abcoronalis protrusus sp. nov. is from Borneo (Malaysia). A checklist and key of the subtribe Paraboloponina from Northern Borneo is provided.